Negative result: Application of Raman spectroscopy to the forensic analysis of an arid, sandy, soil - Newland, Talia G.; Pitts, Kari; Lewis, Simon (2023)
In this study, the application of Raman spectroscopy for the examination of the quartz-recovered fine fraction of arid, sandy soils is presented for the first time. The aim was to explore whether the technique would allow for the initial screening of samples, with the goal to extend the technique to in-situ analysis of the coatings on the quartz grains. Despite investigation of a variety of experimental conditions and different approaches to data correction, Raman analysis of the quartz-recovered fine fraction of sandy soils showed high levels of fluorescence, which masked all potential characterisation data captured within the spectra.